Pohjois-Suomen mikroyritykset:tilastokatsaus - Jokela, H. (Harri); Niinikoski, E.-R. (Eija-Riitta); Muhos, M. (Matti) (University of Oulu, 2016)
Abstract The aim of this study was to investigate the characteristics of enterprises, especially microenterprises, in Northern Finland based on the statistical data. The report is based on the year 2015 data and it is part of the Micro-enterprise Growth Platform project that is financed by the Council of Oulu Region as a European Regional Development Fund (ERDF) project. This report presents statistical information of the enterprises in Northern Finland. Statistical data was purchased from Bisnode Finland Ltd. The data (collected 27 Oct 2015) consists of 49 411 business identity codes registered in Northern Finland in one of the following regions: Kainuu, Lapland and North Ostrobothnia. Closer analysis include business identity codes of the companies that had key information (industrial classification, number of personnel, sales) in the statistical data. The final data contains 47 519 business IDs, which were analyzed in this report using the following variables: legal form, number of employees, turnover, industry, import and export activities and registration year. In Northern Finland almost 96% of companies are micro-enterprises having less than 10 employees. Majority of the micro-enterprises (95.5%) employ less than 5 persons. The share of SMEs in Northern Finland is 99.94%. There are just a few big companies (having 250 or more employees) in Northern Finland (0.06 %). The most common category (25.5 %) of activity (SIC 2008) is a forestry and logging (SIC 02). Approximately 82% of the companies have less than EUR 200 000 sales per year. Almost 43% of the companies having over one million euros turnover are micro-sized enterprises, and 24.4% of the companies having over two million turnover are micro-enterprises. There are 1 724 import companies and 585 export companies in Northern Finland. Almost 52% of the export companies and almost 68% of the import companies are micro-sized in Northern Finland. The average age of the companies in Northern Finland is about 11.5 years. The most common form of the Northern ...